Empowering Agriculture: Exploring Farmers' Perception of Avocado Pameling Innovation in East Java - Edi Dwi Cahyono; Alia Fibrianingtyas; Silvana Maulidah; Fitria Dina Riana; Deana Aulia Juvitasari (Universitas Muhammadiyah Malang, 2024)
Export activities of agricultural commodities in Indonesia present significant opportunities, as evidenced by the implementation of the 'Gratieks' (Three Times Agricultural Export Movement) initiative aimed at bolstering the value of Indonesian agricultural exports. Leveraging this opportunity, the government collaborates with stakeholders in the agricultural industry across regions to foster the development of distinctive commodities. Among these notable products is the Pameling avocado, introduced as an innovative solution to the challenges faced by farmers in Tutur, Pasuruan, East Java, due to its various advantages. This study seeks to examine farmers' perceptions of the Pameling avocado innovation, conducted specifically in Tutur, Pasuruan, East Java. Utilizing a quantitative descriptive analysis approach, the study engaged 40 farmers as respondents. Findings reveal a positive outlook among farmers regarding the Pameling avocado innovation. Notably, indicators such as perceived relative advantage and observability attained a remarkably high rating of 97.8%, followed by the triability indicator (96.5%) and the appropriateness indicator (94.5%). Conversely, the complexity indicator exhibited the lowest score, standing at 26%.